Question

1252) y=(C1)exp(Ax)+(C2)exp(Bx)+F+Gx is the general solution of the second order linear differential equation: (y'') + ( -4y') + ( 3y) = ( 2) + ( -7)x. Find A,B,F,G, where A>B.

Answer #1

1252) y=(C1)exp(Ax)+(C2)exp(Bx)+F+Gx is the general solution of
the second order linear differential equation:
(y'') + ( -9y') + ( 20y) = ( -9) + ( -8)x. Find A,B,F,G, where
A>B. This exercise may show "+ (-#)" which should be enterered into
the calculator as "-#", and not "+-#". ans:4

1249) The solution of some second order linear DEQ is
exp(-1x)[5sin(3x)+ 2cos(3x)] which can also be expressed as
A*exp(-D*x)*sin(F*x+G). Determine A,D,F, and G (degrees). ans:4
1252) y=(C1)exp(Ax)+(C2)exp(Bx)+F+Gx is the general solution of the second order linear differential equation: (y'') + ( -8y') + ( -9y) = ( -8) + ( 3)x. Find A,B,F,G, where A>B. This exercise may show "+ (-#)" which should be enterered into the calculator as "-#", and not "+-#". ans:4

1250) y=Aexp(Bx)+Fexp(Gx) is the particular solution of
the second order linear differential equation:
(y'') + ( 2y') + (-24y) = 0, subject to the boundary conditions:
y=4, and y'=1 when x=0. Find A,B,F, and G, where B>G.

Second-Order Linear Non-homogeneous with Constant Coefficients:
Find the general solution to the following differential equation,
using the Method of Undetermined Coefficients.
y''− 2y' + y = 4x + xe^x

Find the general solution to the first-order linear differential
equation.
y' = -y(6-y)

Find the general solution to the non-homogeneous differential
equation.
y'' + 4y' + 3y = 2x2
y(x) =

Question 11:
What is the general solution of the following homogeneous
second-order differential equation?
d^2y/dx^2 + 10 dy/dx + 25.y =0
(a)
y = e 12.5.x (Ax + B)
(b)
y = e -5.x (Ax + B)
(c)
y = e -10.x (Ax + B)
(d)
y = e +5.x (Ax + B)
Question 12:
What is the general solution of the following homogeneous
second-order differential equation?
Non-integers are expressed to one decimal place.
d^2y/dx^2 − 38.y =0
(a)
y...

Find the general solution of the differential equation:
y''' - 3y'' + 3y' - y = e^x - x + 16
y' being the first derivative of y(x), y'' being the second
derivative, etc.

Show that f(x) = C1e4x +
C2e-2x is a solution to the differential
equation: y’’ – 2y’ – 8y = 0, for all constants C1 and
C2. Then find values for C1 and C2
such that y(0) = 1 and y’(0) = 0.

Find the general solution to the differential equation: y’’ – 6
y’ + 13y = 0
Find the general solution to the differential equation: y’’ +
5y’ + 4y = x + cos(x)

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 40 minutes ago

asked 54 minutes ago

asked 1 hour ago

asked 2 hours ago

asked 2 hours ago

asked 3 hours ago

asked 3 hours ago

asked 3 hours ago

asked 3 hours ago

asked 4 hours ago

asked 4 hours ago

asked 4 hours ago